PEMASARAN KEWIRAUSAHAAN DAN KINERJA PEMASARAN UKM MAKANAN DAN MINUMAN DI JAWA BARAT - Mubarok, Dadan Abdul Aziz; Rahmi, Palupi Permata; Sarah, Siti (ANALISIS, 2023)
This study aims to determine and analyse the effect of entrepreneurial marketing on the marketing performance of small and medium enterprises (SMEs) in the food and beverage sector in West Java Province. The background of the research is that marketing activities as a core of SME activity have not yet optimally contributed to the achievement of marketing performance. The research method by means of explorative research. Entrepreneurial marketing is measured by customer focus, value creation through the network, and closeness to market. Marketing performance is measured by profitability, sales growth and market share. Research variables were measured using a scale of 1- 7. The study population was small and medium enterprises food and beverage sector located in West Java. The research sample of 102 SMEs. Research instruments using a questionnaire. Data analysis using PLS SEM. The results showed that the food and beverage sector SMEs have not been able to apply entrepreneurial marketing so that marketing performance as a benchmark for the success of the marketing strategies and programs implemented has not been able to be achieved by the food and beverage sector SMEs. Data analysis with PLS SEM shows that entrepreneurial marketing influences the achievement of marketing performance in SMEs. The implication of the results of the study explains that entrepreneurial marketing is expected to be a guideline for SMEs marketing strategies and programs to be more focused and value creation through network able to support marketing activities that are carried out closer to the target market and its customers.